EVALUASI PEMANFAATAN TIK SEBAGAI MEDIA PEMBELAJARAN SELAMA COVID-19 DI SLB SE-KOTA PADANG - Septia Rimasari; Marlina Marlina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to evaluate the utilization of technology as a learning medium by special education teachers in Padang during the COVID-19 pandemic. The focus of this research lies on how the utilization of information technology can facilitate the learning process for students with special needs, serve as a teaching tool for teachers, and be adapted to the characteristics of students with special needs during the pandemic. The research method employed is descriptive quantitative, with an online questionnaire used as the data collection technique, which was distributed to 25 special education schools in Padang. The sampling technique applied was purposive sampling. The results of this study indicate that the utilization of information technology to facilitate the learning process during the COVID-19 pandemic fell into the "fairly good" category with a percentage of 55.11%. The utilization of information technology as a teaching tool during the pandemic was also categorized as "fairly good" with a percentage of 58.72%. Meanwhile, the utilization of information technology as a learning medium adapted to the characteristics of students' needs fell into the "poor" category with a percentage of 49.33%. In conclusion, the overall utilization of information technology as a learning medium by special education teachers in Padang during the COVID-19 pandemic was poorly implemented.